Plant bioactives and redox signaling: (–)-Epicatechin as a paradigm - Fraga, César Guillermo (2018)
Polyphenols are bioactives claimed to be responsible for some of the health benefits provided by fruit and vegetables. It is currently accepted that the bioactivities of polyphenols can be mostly ascribed to their interactions with proteins and lipids. Such interactions can affect cell oxidant production and cell signaling, and explain in part the ability of polyphenols to promote health. EC can modulate redox sensitive signaling by: i) defining the extent of oxidant levels that can modify cell signaling, function, and fate, e.g. regulating enzymes that generate superoxide, hydrogen peroxide and nitric oxide; or ii) regulating the activation of transcription factors sensible to oxidants. The latter includes the regulation of the nuclear factor E2-related factor 2 (Nfr2) pathway, which in turn can promote the synthesis of antioxidant defenses, and of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) pathway, which mediates the expression of oxidants generating enzymes, as well as proteins not involved in redox reactions. In summary, a significant amount of data vindicates the participation of EC in redox regulated signaling pathways. Progress in the understanding of the molecular mechanisms involved in EC biological actions will help to define recommendations in terms of which fruit and vegetables are healthier and the amounts necessary to provide health effects.